The quantum theory of magnetism - Majlis, Norberto (World Scientific, 2000)
This book is intended as a basic text for a two-term graduate course for physicists, engineers and chemists with a background in quantum and statistical mechanics. What sets it apart from other publications on the subject is its extensive use of Green's function techniques and its detailed discussion of the application of the mean-field approximation and dipole-dipole interactions in one, two and three dimensions. A chapter each has been devoted to low-dimensional systems, surface magnetism and layered systems. A total of 60 exercises have also been included.